THE ECONOMIC RATIONALE FOR THE USE OF OUTPATIENT PLEURODESIS IN THE TREATMENT OF MALIGNANT PLEURAL EFFUSIONS - O. V. Ivanov; V. N. Klimenko; A. V. Reshetov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2020)
Introduction. Exudative tumor pleurisy affects up to 100 000 people a year in Russia, up to 400 000 people a year in Europe. Inpatient treatment of such patients is associated with certain costs, and there are also queues for treatment in oncology hospitals. An outpatient pleurodesis can reduce these problems.The objective was to compare pharmacoeconomic parameters for inpatient pleurodesis and outpatient pleurodesis to determine the most cost-effective treatment option.Methods and materials. 179 patients in the clinic of the Federal State Budgetary Institution Scientific Research Center for Oncology named after N. N. Petrov of the Russian Ministry of Health underwent pleurodesis using various methods (talc, bleocin, combined). The effectiveness of the methods and the direct medical costs of treatment were evaluated. The effectiveness of a stationary thoracoscopic pleurodesis was evaluated according to foreign literature, and the direct medical costs of treatment were calculated. Based on the obtained results, the pharmacoeconomic indicators of CER and ICER were calculated.Results. Direct medical costs for stationary thoracoscopic pleurodesis amounted to 35056.4 rubles with an efficiency of 89 %. Direct medical costs for outpatient pleurodesis were: for talc pleurodesis – 8051.7 rubles, for bleocin and combined pleurodesis – 11799.2 rubles. CER amounted to: for a thoracoscopic pleurodesis in the hospital – 393.9, for talc pleurodesis – 115.35, for bleocin pleurodesis – 188.7, for combined pleurodesis – 155.8. ICER in relation to stationary pleurodesis was 1406.4 for talc pleurodesis, 877.6 for bleocin pleurodesis, 1748.6 for combined pleurodesis.Conclusion. CER was almost 3 times lower with outpatient pleurodesis, which makes it the most cost-effective option for the treatment of tumor exudative pleurisy. ICER was maximal in combined pleurodesis, which makes it preferred among outpatient pleurodesis options. Based on the obtained data, it can be argued that the use of ambulatory pleurodesis as an initial stage of care for patients with tumor exudative pleurisy is economically justified.